2010
DOI: 10.1007/s10661-010-1728-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals in some wild edible mushrooms collected from Yunnan Province, China

Abstract: Eight heavy metals (Cu, Zn, Fe, Mn, Cd, Cr, Ni, and Pb) in 14 different wild-growing edible mushroom species (Coprinus comatus, Voluariella volvacea, Pleurotus nebrodensis, Hypsizigus marmoreus, Hericium erinaceus, Agrocybe aegerita, Lenfinus edodes, Collybia velutipes, Agaricus bisporus, Russula albida, Clitocybe conglobata, Pleurotus eryngii, Lepista sordida, and Pleurotus ostreatus) collected from Yunnan province, China, were determined by inductively coupled plasma-atomic emission spectrometry after microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 36 publications
12
69
5
1
Order By: Relevance
“…The fruit bodies of P. ostreatus and P. pulmonarius strains were collected from 19 mushroom farms. The tested fruit bodies were obtained from each mushroom grower in several cultivation cycles each year Bernaś et al 2006;Maihara et al 2008;Muñoz et al 2005;Kalač 2010;Costa-Silva et al 2011;Zhu et al 2011) b P. florida (Alam et al 2008;Mallikarjuna et al 2013) c P. djamor (Rodriguez Estrada andRoyse 2007, Guo et al 2007;Lee et al 2009, Mallikarjuna et al 2013 d P. citrinopileatus (Rodrigues et al 2015) e P. eryngii (Rodriguez Estrada andRoyse 2007, Akyüz andKirbağ 2010;Zhu et al 2011) f P. pulmonarius (Oliveira Silva et al 2002;Vetter 2003, 2005, Borovicka et al 2011 in the period 2009-2015. The weight of a single fruit body sample amounted to 1 kg.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…The fruit bodies of P. ostreatus and P. pulmonarius strains were collected from 19 mushroom farms. The tested fruit bodies were obtained from each mushroom grower in several cultivation cycles each year Bernaś et al 2006;Maihara et al 2008;Muñoz et al 2005;Kalač 2010;Costa-Silva et al 2011;Zhu et al 2011) b P. florida (Alam et al 2008;Mallikarjuna et al 2013) c P. djamor (Rodriguez Estrada andRoyse 2007, Guo et al 2007;Lee et al 2009, Mallikarjuna et al 2013 d P. citrinopileatus (Rodrigues et al 2015) e P. eryngii (Rodriguez Estrada andRoyse 2007, Akyüz andKirbağ 2010;Zhu et al 2011) f P. pulmonarius (Oliveira Silva et al 2002;Vetter 2003, 2005, Borovicka et al 2011 in the period 2009-2015. The weight of a single fruit body sample amounted to 1 kg.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Guler and Ozkaya [21] reported that various carbon sources spherical and thick morel sclerotial structures in vitro. In detail, Many studies have reported that suitable concentrations of some minerals, heavy metals and toxic metallic elements play an important role in metabolic processes, during the growth of morel mushrooms [22,23]. In particular, iron, calcium, and magnesium are abundant in several Morchella sp.…”
Section: Resultsmentioning
confidence: 99%
“…The trend in decreasing order of elements present in wild samples was Fe > Zn > Cu > Mn > Pb. Mushrooms are known to possess a very effective mechanism that enables them to readily take up some heavy metals from the ecosystem [27]. The accumulation of heavy metals in mushrooms seems to be affected by environmental and fungal related factors.…”
Section: Resultsmentioning
confidence: 99%